Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1155/2017/6087676
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid Hormone (1-34) Might Not Improve Early Bone Healing after Sinus Augmentation in Healthy Rabbits

Abstract: Purpose. This study evaluated the effect of administering intermittent parathyroid hormone [PTH (1-34), henceforth PTH] on the early-stage bone healing of maxillary sinus augmentation in healthy rabbits. Materials and Methods. Bovine bone mineral was grafted on the sinuses of 20 female New Zealand white rabbits. The animals were randomly divided into two groups, PTH (n = 10) or saline (n = 10), in which either PTH or saline was injected subcutaneously 5 days a week for 2 weeks. Half of the animals in each grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…In our experiments, PTH was administered at 10 μg kg −1 day −1 for 5 weeks (from 1 week before sinus surgery to 4 weeks after sinus surgery) to investigate the effect at a minimum dose over a minimum period. Huh et al () performed bone augmentation in the healthy rabbit sinus, and PTH was injected subcutaneous at a dose of 10 μg/kg for either 2 or 4 weeks, with the comparison showing that bone formation was greater after 4 weeks of administration. However, no significant difference was found between the PTH and saline groups.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our experiments, PTH was administered at 10 μg kg −1 day −1 for 5 weeks (from 1 week before sinus surgery to 4 weeks after sinus surgery) to investigate the effect at a minimum dose over a minimum period. Huh et al () performed bone augmentation in the healthy rabbit sinus, and PTH was injected subcutaneous at a dose of 10 μg/kg for either 2 or 4 weeks, with the comparison showing that bone formation was greater after 4 weeks of administration. However, no significant difference was found between the PTH and saline groups.…”
Section: Discussionmentioning
confidence: 99%
“…Histomorphometric analysis of the detail area revealed that the NBA of window was significantly higher than center. This result was in both experimental and control groups and the same results in previous studies (Huh et al, ; Iida et al, ). This implies that the new bone grew earlier around the graft material near the cortical bone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protocol used in this study for μCT analysis was similar to previous studies (Shiels et al, 2012). At 8 weeks (Huh et al, 2017;Kuroshima, Yasutake, Tsuiki, Nakano, & Sawase, 2015;Mashiba et al, 2001;Wen et al, 2015) after surgery (post-euthanasia) for bone remodeling assessment, μCT images were taken using a Skyscan 1076 (Kontich, Belgium) with 8.77 μm resolution. The femurs were fixed using a 10% formaldehyde solution.…”
Section: Micro-ct (μCt) Characterizationmentioning
confidence: 99%
“…Many treatment options have been considered to overcome these issues. Studies have suggested that non‐surgical maxillary treatments such as hyperbaric oxygen (HBO) and parathyroid hormone (PTH) can be used to treat bone diseases in which osteogenic potential is severely impaired (Huh et al, ; Mericske‐Stern et al, ) and also in cases where a poor prognosis is expected even after use of bone graft materials (Atalay et al, ; Bashutski et al, ; Cheung & Seeman, ; Gerard, Carlson, Gotcher, & Pickett, ; Scoletta, Arduino, Reggio, Dalmasso, & Mozzati, ; Vescovi et al, ).…”
Section: Introductionmentioning
confidence: 99%